Funkcioniranje prometnog sustava u izvanrednim uvjetima - Kolenc, Jurij; Cvetanović, Lazar; Zorić, Nikola (Promet - Traffic&Transportation, 2012)
The existing concept of the transportation system operation is not in many of its segments adequately suited to the requirements of efficient functioning in all situations. This paper provides recommendations for the improvement of the accepted concept by means of defined internal and external requirements and respective basic objectives for the improvement of the operation concept.